Optimal Policies for Conjunctive-Use and Cropping Pattern for Al-Wand Basin - Al-Haddad, Amer Hassan; Jabal, Zainab Kadhim (Al-Nahrain Journal for Engineering Sciences, 2017)
Applying conjunctive use between surface water and ground water is getting widely used at many regions in the world, due to the increasing need of water resources, especially when large quantities of water and for long time are used for irrigation purposes to meet agricultural production requirements.The linear programming has been formulated to optimize the optimum allocation of water. An economic analysis of conjunctive use for Al-Wand project in Iraq has been done for a certain cropping pattern using two scenarios of management and operation of ground water and surface water. One suggested scenario was to use ground tank to save the water during the period of water excess to be used during the shortage period. The other scenario was to operate the reservoir dam to supply the water requirements during the agriculture years. The main concerns of this research were: the fluctuation of the ground water and how to estimate the deficit of yield which is caused by using the decreased water in irrigation. The economic analysis has been done by calculating the overall cost and the annual estimation of return. It can be concluded that the operation of surface water at (60 and 70%) from total available surface is a compromise, because some of the water still flow in the river and canals and the ground water reservoirs were not affected especially its storage capacity.